An Immunoregulatory Role of Interleukin-3 in Allergic Asthma - Krammer, Susanne; Yang, Zuqin; Zimmermann, Theodor; Xepapadaki, Paraskevi; Geppert, Carol I.; Papadopoulos, Nikolaos G.; Finotto, Susetta (Frontiers in Immunology, 2022)
Background Allergic asthma is a chronic airway inflammatory disease associated with airway mucus hyper-production. ILC2 cells, which express the Th2 transcription factor GATA3, have been associated with allergic asthma. The cytokine IL-3 is known to support eosinophil, basophil and mucosal mast cell differentiation and survival; however, its role on T regulatory cells as well as on lung ILC2 and in pediatric asthma needs further investigation. Objectives To investigate the role of IL-3 in preschool children and to explore its therapeutic role in experimental asthma. Methods In a cohort of preschool children with and without asthma, we analyzed the secretion of IL-3 in nasopharyngeal fluid (NPF) and IL-3 receptor (R) alpha chain mRNA expression in peripheral blood mononuclear cells (PBMCs). In a murine model of allergic asthma, we analyzed the phenotype of wild-type untreated and rIL-3 intranasally treated asthmatic mice. Results IL-3 was found downregulated in the nasopharyngeal fluid of children with partially controlled asthma, as compared to control children. Moreover, IL-3 was found induced in phytohemagglutinin (PHA)-stimulated PBMCs from children with asthma and treated with steroids. Finally, IL-3 in NPF directly correlated with the anti-inflammatory molecule sST2 in steroid-treated asthmatic children. Intranasal rIL-3 delivery in vivo during the challenge phase decreased airway mucus production and inflammatory eosinophils. Moreover, rIL-3 given during the challenge phase, reduced lung ST2intGATA3+ILC2, accompanied by an induction of T regulatory cells in the airways. Conclusions IL-3 was found associated with steroid-resolved asthma. Moreover, treatment with rIL-3 resulted in amelioration of airway eosinophilia and mucus production, two main pathophysiological conditions associated with asthma in a murine model of allergic asthma. Thus, rIL-3 opens new strategies for immunotherapy of this disease.